Evaluation of sugarcane smut resistance in wild sugarcane (Saccharum spontaneum L.) accessions collected in Japan. (3rd April 2019) - Sakaigaichi, Takeo; Terajima, Yoshifumi; Matsuoka, Makoto; Irei, Shin; Fukuhara, Seiji; Mitsunaga, Takayuki; Tanaka, Minoru; Tarumoto, Yusuke; Terauchi, Takayoshi; Hattori, Taiichiro; Ishikawa, Shoko; Hayano, Michiko
ABSTRACT: Sugarcane smut, caused by Sporisorium scitamineum, is one of the most important sugarcane diseases in Japan. Wild sugarcane, Saccharum spontaneum, is known to be a key breeding material to obtain high-yielding clones. In this study, we sought to identify Japanese wild sugarcane accessions with high resistance to smut. Thirty wild sugarcanes and three sugarcane cultivars were tested by the pinprick method. The results of the inoculation tests aided in identifying wild sugarcanes with high resistance to smut disease, namely JW90, Iriomote8, and Iriomote15. After screening the germplasm, progeny distribution of smut resistance from the inoculation test and dry matter productivity in the smut disease-free field were compared. The highly resistant wild sugarcane accession had a much better impact on progeny distribution of smut resistance compared with the susceptible accession. No relationship was found between smut resistance and dry matter productivity in both populations.